Gaigeria pachyscelis Railliet & Henry, 1910 (nematoda: ancylostomatidae) , parasito de caprinos no Estado de São Paulo, Brasil - Arantes, Isaú Gouveia; Nascimento, Adjair Antonio do; Gonçalves, Ernani Ibirá; Guerra, Laeir (Revista do Centro de Ciências Rurais, 2008)
Os autores efetuaram estudo morfológico em 20 exemplares machos e em 20 exemplares fêmeas de Gaigeria pachyscelis, oriundos de caprinos naturalmente infestados, procedentes do Município de Paulo de Faria, Estado de São Paulo, Brasil. Cápsula bucal subglobular contendo, no fundo 2, lancetas subventrais com 3 a 5 pontas em seus rebordos e um pequeno dente dorsal. Os raios externo-dorsais da bolsa copuladora apresentam leve assimetria em sua inserção com o raio dorsal, que se bifurca aproximadamente na metade da distância entre a base e a extremidade duas bifurcações terminais. Bifurcações estas que possuem em seus rebordos 3 pequenas nodulações ou digitações. Espículos longos, delgados, com bainha. Apresentam em quase toda a sua extensão, franja de estrias semelhantes a pêlos de barba, excetuando-se a metade distal recurvada do terço posterior. Gubernáculo ausente.AbstractThe authors carried out a morphologic study of 20 male and 20 female of Gaigeria pachyscelis from goats with a natural infestation in the county of Paulo de Faria, SP, Brazil. They presented, subglobular buccal capsule, with two lancets on the bottom, with 3 to 5 points on its edges and a little tooth. The external-dorsal rays of the joining puch, presented a light asymmetry on its insertion with the dorsal ray, that branched nearly at the half of the distance between the base and the extremity of the two terminals bifurcations. These bifurcation presented on its edges 3 1ittle nodulations or fingerings. Long spicules, well chitinized thin and with sheath, showing 3 differents portions that correspond to one third. In the proximal portion the spicules are separated, in the middle together and in the distal portion again separated. In the proximal third, each spicule present the form of a wing, internally, delimited by one side by t h e s p i c u l e and by t h e o t h e r by a f r i n g e form o f grooves that are similar to "cilium" or beard. The wings did not reach the vertex of the angle form by the front of the spicules branches. In the middle third, in wich the spicules are goin exist in the lateral edge of each spicule a fringe of grooves similar at in the proceding third. On the distal third , where the spicules are separated is just the same as in the middle third, fringe of grooves only on the region were the spicules are separated. The distal part of this third have not grooves, in thin and presented an internal curve, that finish in one point.